A new perspective on delusional states: Evidence for claustrum involvement - Patru, Cristina M.; Reser, David (Frontiers in Psychiatry, 2015)
Delusions are a hallmark positive symptom of schizophrenia, although they are also associated with a wide variety of other psychiatric and neurological disorders. The heterogeneity of clinical presentation and underlying disease, along with a lack of experimental animal models, make delusions exceptionally difficult to study in isolation, either in schizophrenia or other diseases. To date, no detailed studies have focused specifically on the neural mechanisms of delusion, although some studies have reported characteristic activation of specific brain areas or networks associated with them. Here we present a novel hypothesis and extant supporting evidence implicating the claustrum, a relatively poorly understood forebrain nucleus, as a potential common center for delusional states.